2023
DOI: 10.1002/ajh.26987
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary factors and time of day on iron absorption from oral iron supplements in iron deficient women

Abstract: Guidelines generally recommend taking iron supplements in the morning away from meals and with ascorbic acid (AA) to increase iron absorption. However, there is little direct evidence on the effects of dietary factors and time of day on absorption from iron supplements. In iron‐depleted women (n = 34; median serum ferritin 19.4 μg/L), we administered 100 mg iron doses labeled with 54Fe, 57Fe, or 58Fe in each of six different conditions with: (1) water (reference) in the morning; (2) 80 mg AA; (3) 500 mg AA; (4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 45 publications
0
9
0
1
Order By: Relevance
“…We have done sensitivity analysis to show that baseline hemoglobin level does not affect the result. Although, iron absorption from the different ferrous formulation was about the same and mainly affected by dietary habits, to account for any variation in absorption, we have adjusted our model with different iron formulations and PPI . Because decreased kidney function is known to affect oral iron absorption, we have studied patients with CKD as a separate subcohort.…”
Section: Discussionmentioning
confidence: 99%
“…We have done sensitivity analysis to show that baseline hemoglobin level does not affect the result. Although, iron absorption from the different ferrous formulation was about the same and mainly affected by dietary habits, to account for any variation in absorption, we have adjusted our model with different iron formulations and PPI . Because decreased kidney function is known to affect oral iron absorption, we have studied patients with CKD as a separate subcohort.…”
Section: Discussionmentioning
confidence: 99%
“…Many adolescents ask about taking iron with foods to decrease gastrointestinal side effects. A recent study demonstrated that 100 mg iron consumption with coffee alone and breakfast decreases iron absorption by 54% and 66%, respectively [ 74 ]. The impact of coffee and tea ingestion on iron absorption is important to keep in mind for adolescents who have or are at risk of ID, especially those who are receiving iron supplementation.…”
Section: Oral Iron Supplementationmentioning
confidence: 99%
“…The study reported that consuming the iron supplement in the morning with orange juice alone resulted in an approximately four-fold increase in iron absorption compared to taking the iron supplementation with coffee or during breakfast. They concluded that the maximum efficacy of oral iron supplementation was reported when ferrous iron supplements were taken in the morning, away from meals or coffee, and preferably with an AA-rich food or beverage [58].…”
Section: Oral Iron As Treatment For Iron Deficiency and Iron Deficien...mentioning
confidence: 99%